Trends in Absolute Poverty in Pakistan: 1990-91 and 2001 (The Pakistan Development Review, 2002)
Poverty, defined comprehensively as absence of options to shape one’s life according to one’s own preferences, comes closer to the concept of human development as presented in UNDP’s Human Development Reports. Absolute poverty, on the contrary, defines poverty in terms of satisfaction of minimum physical needs of food and non-food items to enable people at the lower end of income distribution to engage in economic activity. From the vantage point of the policy-maker concerned with alleviation of poverty, it is crucial to know the magnitude of the existing level of poverty and identify the policy determinants of poverty as well as constraints standing in the way of an effective attack on the worst forms of absolute poverty. In Pakistan, like many other developing countries, poverty has emerged as a core issue on the policy agenda. The traditional measures of poverty—headcount, severity and poverty gap indicate that the incidence of poverty during the previous decade have shown no sign of poverty abatement despite numerous policy and institutional initiatives undertaken by the government. The debate on trends in poverty during the 1990s—an era of stabilisation and structural adjustment has been wide-ranging in Pakistan. However, there is no consensus on the poverty outcomes from the policy and institutional reforms. Primarily due to non-availability of basic data, the last year for which poverty estimates are available is 1998-99.